The Relationship between Distance of Pregnancy and Parity with The Incidence of Preeclampsia in RSUD dr. M. Yunus Bengkulu - Desi Fitriani; Waytherlis Apriani; Putri Sari (Jurnal Sains Kesehatan, 2019)
The impact of preeclampsia is low birth weight (LBW) and death in mothers. This study aims to study the relationship between distance of pregnancy and parity with the incidence of preeclampsia in RSUD dr. M. Yunus Bengkulu in 2018. This study uses an Analytical Survey approach with a case control design. The population is all non-primiparous maternity mothers in RSUD Dr. M Yunus Bengkulu In 2018 as many as 342 people consisted of 51 case variables of mothers who had preeclampsia taken in total sampling and 51 control variables of non preeclampsia mothers taken by systematic random sampling with multiples of 6. Data collection is using secondary data by looking at documentation data using cheklis. Data analysis was performed with the Chi-Square (χ2) test, Contingency Coefficient (C) Test and Odd Ratio (OR). The results obtained:  Of the 102 ibu, there were 51 mothers preeclampsia and 51 mothers not preeclampsia, 36 pregnancy distances 2 years, 66 people pregnancy distances ≥ 2 years, 63 people (38.9%) primiparous or grandemultiparous parity, 99 people (61.1%) multiparous parity, there is a significant relationship between the distance of pregnancy with the incidence of preeclampsia in RSUD dr. M. Yunus Bengkulu, with a moderate relationship category, and there is a significant relationship between parity and the incidence of preeclampsia in RSUD dr. M. Yunus Bengkulu, with medium relationship category. It is hoped that health workers will further enhance health promotion about the effects of pregnancy spacing and parity on preeclampsia. Keywords: pregnancy distance, parity, preeclampsia